Electrical Anisotropy of Thin Metal Films Growing on Dielectric Substrates - Jakučionis, L.; Kleiza, V. (Nonlinear Analysis: Modelling and Control, 2002)
Electrical properties of conductive thin films, that are produced by vacuum evaporation on the dielectric substrates, and which properties depend on their thickness, usually are anisotropic i.e. they have uniaxial anisotropy. If the condensate grow on dielectric substrates on which plane electrical field E is created the transverse voltage U⊥ appears on the boundary of the film in the direction perpendicular to E. Transverse voltage U⊥ depends on the angle γ between the applied magnetic field H and axis of light magnetisation. When electric field E is applied to continuous or grid layers, U⊥ and resistance R of layers are changed by changing γ. It means that value of U⊥ is the measure of anisotropy magnitude. Increasing voltage U0 , which is created by E, U⊥ increases to certain magnitude and later decreases. The anisotropy of continuous thin layers is excited by inequality of conductivity tensor components σ0 ≠ σ⊥. The reason of anisotropy is explained by the model which shows that properties of grain boundaries are defined by unequal probability of transient of charge carrier.
Keywords: thin films; uniaxial anisotropy; conductivity